IMPACT OF COMBINE HARVESTER SPEED ON WHEAT GRAIN LOSS: A FIELD STUDY IN MULTAN, PAKISTAN - Khaliq, A.; Qasim, M. Z.; Ahmad, F.; Mahmood, H. S.; Cuong, D. M. (Pak. J. Agri. Engg., Vet. Sci., 2024)
Wheat (Triticum aestivum) is the most important staple crop with a demand-based need to ensure food security but faces the challenges of timely harvesting at crop maturity. Harvesting operation of the wheat crop is one of the major activities during crop production and is important for food security and sustainability. The study's main purpose is to investigate the impact of vehicle speed on wheat grain losses during the harvesting operation. Varied speeds of the combine harvester were observed during the field tests and measured the grain losses by using a designed sampling method. The field observation recorded that the normal working speeds of the combine harvester were in a range of 7.54 km/hr to 11.77 km/hr during field tests with an average of 9.59 km/hr. The average grain losses were noted at 49.80 kg acre-1 with a percentage of 2.49% of total grain production in one acre. The highest grain losses were 69.11 kg acre-1 with a 3.46% percentage, identified at a vehicle speed of 11.77 km/hr, while the lowest at 7.54 km/hr that 35.35 kg acre-1 with a 1.76% percentage loss. Threshing losses significantly influenced the overall grain loss, which ranged from 1% to 1.8%, with specific grain damage from 0.36% to 1.07%, and shattering losses ranging from 0.4% to 0.65% due to variable vehicle speeds. The outcomes of the study found that field speed had a linear relationship with grain loss. Conclusively, the research findings provide guidelines to the machine operators and farmers should optimize the working speed to minimize grain loss during wheat harvesting.